Links between Adolescents’ Health Literacy and their Physical Activity and Body Mass Index (Baltic Journal of Sport and Health Sciences, 2019)
Background. The aim of the study was to identify links between health literacy, health information literacy and physical activity as well as body mass index in adolescents.Methods. The study was carried out from September till the end of November, 2018. Research participants were 167 14–18-year-old students from Kaunas, Klaipeda and Vilnius (n = 107 females, n = 60 males). Participants were asked to fill in an anonymous online questionnaire, which consisted of basic demographics, physical activity, health information literacy and health literacy. Adolescents’ body mass index was calculated using ISO-BMI calculations. Physical activity was assessed by Petronytė’s physical activity questionnaire. To determine adolescents’ everyday health information literacy, we used self-assessed 10-item screening tool (EHIL-10) and to determine health literacy, we used Newest Vital Sign (NVS) screening test. Data analysis was performed using SPSS 23.0 program for Windows.Results. Health literacy did not have association with body mass index or the level of physical activity. Health literacy scores gave important data of the level of health literacy. The scores indicated that 21.6% of Lithuanian adolescents had adequate level of health literacy. It was found that age correlated positively with health literacy. Self-assessed everyday health information literacy was higher since 85% of the students had medium high or high level of health information literacy. The data revealed that adolescents were not sure where they could find health related information and who they could trust in health-related issues. For males, finding health information and knowing who they could trust in health issues was easier than for females. Health information literacy did not have association with ISO-BMI. Sufficient evaluation of health-related information was higher among normally weighted adolescents. Physically active students had higher health information literacy and participation in sports club activities had positive relation with better health information literacy. Additionally, involvement in organized activities associated with superior understanding of terms and sentences of health information. Evaluation of health information was higher among those who were actively involved in organized physical activities.Conclusions. Health information literacy did not have association with ISO-BMI. Those, who were involved in sports club activities or were more actively involved in organized physical activities had better health information literacy and evaluation of health information. Nevertheless, there was no connection between health literacy and physical activity. Keywords: health literacy, health information literacy, physical activity, body mass index.